Connect To Care (C2C): protocol for two-site randomized controlled pilot trial to improve outcomes for patients with hazardous drinking and PTSD and/or depression symptoms - Michael A. Cucciare; Kathy Marchant; Cristy Benton; Deanna Hildebrand; Sharfun Ghaus; Xiaotong Han; Ronald G. Thompson; Christine Timko (Addiction Science & Clinical Practice, 2023)
Abstract Background In studies of the general population and of military veterans, many primary care patients with hazardous drinking and PTSD and/or depression (abbreviated here as HD +) do not initiate or engage with alcohol-related care. To address this gap in care, we identified and will pilot test a promising evidence-based intervention, Connect To Care (C2C). C2C is a strengths-based approach, delivered by a Care Coach by telephone and/or video, with four components: (1) identifying and leveraging patient strengths to facilitate care initiation, (2) collaborative decision-making around a menu of care options, (3) identifying and resolving barriers to care, and (4) monitoring and facilitating progress toward care initiation by, for example, checking on barriers, identifying solutions, and revisiting care options. Methods/Design Aim 1 will involve adapting C2C for use in Veterans Affairs’ (VA) primary care. We will use an iterative process that includes focus groups and semi-structured interviews with key stakeholders (patients, primary care providers, and VA national policy leaders). In Aim 2, we will conduct a two-site, pilot randomized controlled trial to determine the feasibility of conducting a larger scale trial to test C2C’s effectiveness, ascertain the acceptability of C2C among primary care patients with HD + , and explore the efficacy of C2C to improve veteran patients’ initiation of and engagement in alcohol care, and their alcohol and mental health (PTSD, depression) outcomes, at 3-month follow-up. We will explore explanatory mechanisms by which C2C is effective. Discussion Study findings are likely to have implications for clinical practice to enhance current approaches to linking patients with HD + to alcohol care by applying a practical intervention such as C2C. The results may improve treatment outcomes for people with HD + by drawing on patients’ strengths to problem-solve barriers to care following a process of shared decision-making with a coach. In addition to possibly accelerating the translation of C2C into practice, study findings will also support additional research in terms of a planned effectiveness-implementation hybrid trial, adding to this study’s potential for high impact. Trial registration: ClinicalTrials.gov Identifier: NCT05023317.